PUBLIC RELATIONS AS A MAIN PILLAR IN IMPROVING AND STRENGTHENING LIBRARY IMAGES - BAKHTIYAR (JURNAL EKONOMI, SOSIAL & HUMANIORA)
The purpose of the study is to know: (1). the role of public relations in improving and strengthening the library’s image. (2). The role of higher education libraries in supporting sustainable development. The research object rests on the content discussion of the role of library public relations to improve the image of the library. This research focuses on manifesting the role of libraries in supporting sustainable development. This study uses a historical approach characterized by critical research on shifting thinking. Primary information sources are used for primary data, data collection methods utilize library research. Research analysis uses qualitative descriptive analysis and content analysis to analyze the meaning of the concept of the role of librarians and libraries in substainable development and application of public relations in library organizations. Observations made aimed at supporting theoretical construction. The results of the study are; (1). The role of librarians as Public Relations in enhancing and strengthening the library’s image by implementing; (a) internal communication that is moving all employees to provide the best service, work productively and efficiently, (b). External communication is carried out through making prescriptions according to the needs of journalists and providing maximum services. (2). The role of higher education libraries in supporting sutainable development is; (a). The library provides access to quality information in order to improve the quality of life and social welfare (b). Libraries provide excellent information services quickly, precisely, can and cheaply. (c). The library prepares superior, reliable and quality human resources in the mastery of information.